What Works to Reduce Inequality in Higher Education? - Geven, Koen; Herbaut, Estelle (International Higher Education, 2019)
Policy makers are increasingly searching for ways to reduce inequality in higher education. There is now a sizeable and high-quality body of literature that estimates the effects of interventions on access and completion in higher education. Our new paper reviews 75 quasi-experimental studies and rigorously compares more than 200 causal effects of outreach and financial aid interventions on disadvantaged students. We found that outreach and financial aid can both work, but important lessons should be learned from interventions that do not show an effect. In this article, we first provide an overview of the main mechanisms driving exclusion, both in terms of access to and completion from higher education. We then summarize the evidence for policy makers, highlighting key lessons, while we also indicate directions for future research.